Multimodality approach to treat calciphylaxis in end-stage kidney disease patients - Chloé Lajoie; Abdelaziz Ghanemi; Kateri Bourbeau; Aboubacar Sidibé; Yue-Pei Wang; Simon Desmeules; Fabrice Mac-Way (Renal Failure, 2023)
A multimodality approach has been proposed as an effective treatment for calciphylaxis in patients with end-stage kidney disease. In this retrospective study, we report the cases of 12 end-stage kidney disease patients from l’Hôtel-Dieu de Québec hospital (Canada) who were diagnosed with calciphylaxis between 2004 and 2012 and treated with a multimodality clinical approach including sodium thiosulfate (STS). Statistical analyses were performed to evaluate the impacts of patients characteristics, the different interventions as well as therapy regimen on the therapeutic response. The majority of patients (n = 9) were hemodialyzed. The patients-associated comorbidities were consistent with previously reported risk factors for calciphylaxis: Diabetes (n = 11), calcium-based phosphate binders use (n = 10), warfarin use (n = 9), obesity (n = 7), female gender (n = 8) and intravenous iron use (n = 8). STS was given for a median duration of 81 days. 75% of the patients had a response (total or partial) including a complete response in 42% of patients. One-year mortality rate was low (25%). STS was used during a mean duration of 83.33 ± 41.52 days and with a total cumulating dose of 1129.00 ± 490.58 g. The recorded mean time before a complete response was 102.20 days (51–143). Pain improvement occurred after a mean time of 8.67 ± 10.06 days. None of the studied factors was statistically associated with a complete or a partial response to the multimodality approach. Although our data have a limited statistical power, they support treating calciphylaxis with a multimodality approach including STS as its effects are independent from important clinical variables.